Selectively recovering scandium from high alkali Bayer red mud without impurities of iron, titanium and gallium - 刘召波 宗燕兵 李宏煦 贾东民 赵子晗 (Journal of rare earths, 2017)
Experimental results here can give some new insights into the mechanism of selective recovery of scandium and sodium from high alkali Bayer red mud（RM） through sulfation-roasting-leaching process. Effects of roasting and leaching conditions including roasting time, roasting temperature, concentrated H_2SO_4 addition, leaching temperature, leaching time and liquid to RM solid ratio on the leaching rates of calcium, iron, aluminum, silicon, sodium, titanium, scandium and gallium were studied and analyzed, suggesting that roasting temperature and roasting time were the two primary constraints on selective recovery of Sc and Na. High leaching temperature also brought a negative effect on the iron leaching rate. Phase transitions and thermal behaviors of sulfated RM indicated that sodium had an inhibitory action on the liberation of SO_2 or SO_3 from metal sulfates, which should follow the decomposition order of TiOSO_4〉Ga_2（SO_4）_3〉Fe_2（SO_4）_3〉NaFe（SO_4）_2〉NaAl（SO_4）_2~Al_2（SO_4）_3〉Na_3Sc（SO_4）_3〉Na_2SO_4〉CaSO_4. After water leaching, solid-liquid separation could be carried out extremely smoothly and 〉95 wt.% Na＋, ~60 wt.% Sc in [Sc（H_2O）_x（SO_4）_n]~（3–2n）（x≤6） with impurities of 0 wt.% Fe~（3＋）, 0 wt.% Ti4＋, 0 wt.% Ga~（3＋）, 7 wt.% Al~（3＋）, ~29 wt.% Ca~（2＋） and ~3 wt.% Si~（4＋） could be leached into leachant under the optimized roasting and leaching conditions. The alkali-free residue obtained could then be employed as iron-making or building materials.